Theoretical Study of Hydrotreating Process in Small Heterocyclic Rings - Hafied, M. (Asian Journal of Chemistry, 2015)
A theoretical investigation has been made by use of DFT-B3lyp/cc-pvdz calculation levels, to clarify at the atomic scale of the hydrotreating process which depends on the removal of sulfur, nitrogen and oxygen atoms from the small heterocyclic rings such as thiirane, aziridine and oxyrane. Activation of C-S, C-N and C-O bonds has been done via a simple and a double protonation followed by a full optimization of geometry. Critical points on the potential energy surface, of the protonated systems, were located by use of the frequency calculation. Present results indicate that the small protonated heterocyclic rings have revealed a carbocationic system as organic reactive intermediates presented by a complex with a weak interaction. In addition, proton affinities and charge delocalizations based on NBO analysis have been taken to check the ability of the lone pair of heteroatoms to participate in the formation of H-S, H-N or H-O bonds.